Pengembangan Media Pembelajaran Berbasis Multimedia pada Materi Elemen-Elemen Struktur Bangunan: Penelitian - Lase, Anugerah; Harefa, Envilwan Berkat; Telaumbanua, Aprianus; Telaumbanua, Arisman (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aimed to develop multimedia-based instructional media for the Elements of Building Structures subject at SMK Negeri 1 Tugala Oyo and to examine its feasibility, practicality, and effectiveness. Using the Research and Development (R&D) method with the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), the research involved 16 Grade X DPIB students. Instruments included expert validation questionnaires (content, language, media/design), student and teacher response questionnaires, and learning outcome tests. The results showed that the media met the highly feasible criteria, with validation scores from content and media/design experts improving from 80% to 100%, and language experts from 58.18% to 85.45%. Practicality tests scored 89.33% (individual), 95.08% (small group), and 93.33% (teacher), all in the highly practical category. Effectiveness tests indicated 100% mastery with an average score of 96.53%. The media is thus highly feasible, practical, and effective, offering an innovative alternative for vocational education aligned with the construction industry’s needs.